EFFECT OF KOH CONCENTRATION AND OIL TYPE ON LIQUID DISH SOAP FROM USED COOKING OIL WITH ANTIBACTERIAL EVALUATION - Safira Kanza; Zahrotul Awwelina; Zahra Najma Atika; Burhan; Yuni Nurfiana (Fakultas Teknologi Pertanian Universitas Brawijaya, 2026)
The increasing generation of used cooking oil (UCO) as food waste presents significant environmental challenges while offering opportunities for value-added utilization within a circular economy framework. This study evaluated the effect of potassium hydroxide (KOH) concentration on the quality and microbial characteristics of liquid soap produced from UCO with added orange essential oil. Prior to saponification, UCO was purified using 2% activated charcoal to reduce impurities and undesirable odors. Liquid soap formulations were prepared using three KOH concentrations (20%, 30%, and 40%) and three oil types, namely fresh cooking oil, untreated UCO, and purified UCO. The quality of the liquid soap was assessed based on physicochemical parameters, including homogeneity, pH, specific gravity, viscosity, and total plate count. Antibacterial activity was evaluated against Escherichia coli and Staphylococcus aureus using standard microbiological assays. The results showed that increasing KOH concentration was associated with higher pH, viscosity, and improved homogeneity of the liquid soap. Soap formulated with 40% KOH exhibited more stable physicochemical characteristics compared with those of the lower concentrations. Purification of used cooking oil appeared to enhance oil reactivity during saponification, resulting in more consistent soap properties. The addition of orange essential oil did not produce a clear inhibition zone. It was, however, associated with lower total plate count (TPC) values, indicating a potential role in microbial growth suppression.